The synergistic effect of non-thermal techniques and modified atmosphere packaging in food preservation - Hassan, Farazia; Anwar, Sehar; Mukesh, Mukesh; Munam, Hafiz Abdul; Asjad, Muhammad Arslan; Hussain, Mudassar; batool, Zahra; Khan, Nauman; Khalid, Muhammad Umair (International Journal of Environment, Agriculture and Biotechnology, 2023)
Consumer’s demand for food products that retain the natural properties and microbiologically safer food has promoted the use of non-thermal techniques for the reduction of microbial load and inactivation of enzymatic activity. However, the bacterial spores and some enzymes show high resistance against non-thermal techniques. Therefore, the application of non-thermal techniques with modified atmosphere packaging (MAP) represents an emerging method to increase the shelf life of food products. These combined preservation techniques reduced the microbial load, increase the shelf life without effecting the sensory attributes of food products. The surface of food products would benefit from the preservative effect of both non-thermal techniques and MAP. These integrated techniques are more energy efficient and better preservative effect than the single preservation technique. The use of MAP with non-thermal techniques reduces the intensity of nonthermal treatments required to achieve the desirable results. This review discusses the advantages that may be derived from the combined use of non-thermal techniques and MAP in the preservation of food.